2004
DOI: 10.1002/chem.200305516
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Organic Molecules and Water: Rotational Spectrum of the 1:1 Oxetane–Water complex

Abstract: The 1:1 molecular complex between oxetane and water has been investigated by using free-jet millimeter-wave spectroscopy. The rotational spectra of five isotopomers (with H(2)O, D(2)O, DOH, HOD and H(2) (18)O) have been assigned. Partial r(0) and r(s) structures of the complex have been derived. The water moiety lies in the plane of symmetry of oxetane, with the "free" hydrogen E with respect to the ring. The oxetane ring appears to be slightly nonplanar, with the C(beta) carbon tilted on the opposite side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…[9][10][11][12] The experimental value of the angle aO-H···O, 1718, coincides with the theoretical value (see Table 4). …”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…[9][10][11][12] The experimental value of the angle aO-H···O, 1718, coincides with the theoretical value (see Table 4). …”
Section: Resultssupporting
confidence: 74%
“…As a consequence, splittings are observable in the pure rotational spectra, [1,3] from which information on the potential-energy surface is obtained. When water acts as a proton donor towards weak proton acceptors, such as a fluorine or chlorine atom, or a p system, the water moiety has a considerable dynamic freedom, which still produces features in the microwave (MW) spectrum, as in the cases of difluoromethane-W, [6] chlorofluoromethane-W, [7] and benzonitrile-W. [8] Finally, when water acts as a proton donor and forms strong hydrogen bonds, such as OÀH···O, [9][10][11][12] OÀH···N, [5,[13][14][15][16] or O À H···S, [17] the water moiety is blocked and no splitting due to its internal dynamics is observed. Some exceptions have been observed, however: 1) in the case of dimethylether-W, [18] the W molecule tunnels between the two lone pairs of the ether oxygen, generating large tunnelling splittings; 2) in anisole-W, [19] the W moiety is delocalized while forming secondary interactions with the adjacent methyl or phenyl hydrogen atoms, allowing tunnelling of the water hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The stronger character of the alcohol HB is apparent in the geometry of the complex, with the water oxygen considerably displaced with respect to the furfuryl plane and shorter hydrogen bond distances to the alcohol group ( r (OH⋅⋅⋅O w )=1.956(3) Å vs. r (O w H⋅⋅⋅O r )=2.16(1) Å in Figure ). The O−H⋅⋅⋅O w hydrogen bond distance is close to that observed in the gas‐phase for water adducts with cyclic ethers and alcohols, where only a main HB is formed (ethylene oxide: 1.92(1) Å; propylene oxide: 1.908(7) Å; oxetane: 1.86(2) Å; tetrahydropyrane: [35] 1.91(2) Å; 1,4‐dioxane: 1.90(3) Å; tert ‐butyl alcohol:1.903 Å). In the FM hydrate the situation is reversed, as shown in the bonding distances and the oxygen position, now closer to the furfuryl ring.…”
Section: Discussionsupporting
confidence: 65%
“…There has been some theoretical research carried out on the electronic structure of oxetane. Most work has been focused on calculating the structural properties of monomers and complexes, [15][16][17][18] or the reaction mechanisms of pyrolysis [19][20][21] and photolysis [22][23][24] of oxetane. Ferreira et al 15 predicted the structural stability of a complex of the oxetane monomer with hydrogen halide and discussed the special nature of the weak interaction using density functional theory calculations at the B3LYP/6-311++G(d,p) level.…”
Section: Introductionmentioning
confidence: 99%
“…Ferreira et al 15 predicted the structural stability of a complex of the oxetane monomer with hydrogen halide and discussed the special nature of the weak interaction using density functional theory calculations at the B3LYP/6-311++G(d,p) level. Ottaviani et al 16 computed the electronic structure of oxetane hydrate and gave the geometry and main bond parameters by combining the jet millimeter wave spectrum with quantum chemical calculations. Earlier, Chen et al 19 explored the pyrolysis reaction mechanism of oxetane using a semi-empirical molecular orbital method, and indicated that the biradical reaction was the most interesting process in the variety of primitive reaction pathways.…”
Section: Introductionmentioning
confidence: 99%